O paraíso revisitado de Paulo Henriques Britto e outros Paraísos - Landim, Henrique Soares (2013)
This dissertation aims at carrying out a study about Paraísos artificiais, written by Paulo Henriques Britto, mainly considering the construction of spaces in the short-story, which can be divided into two parts: in the first one, the environment is widely enclosed, the characters can barely move, and it is composed by 5 narratives: Os paraísos artificiais , Uma doença , Uma visita , Um criminoso and O companheiro de quarto . These shortstories are, according to Paulo Henriques Britto, constructed under Samuel Beckett s viewpoint, due to the immobilism, isolation and incommunicability of the characters portrayed in it. In the second part of the book, we have the characters moving in relatively large places, their involvement with the external world, in almost all narratives the protagonist realizes a different type of travel, what is not observed in the five first short-stories. The narratives which compose the second part of the book are Coisa de família , O 921 , O primo , and Os sonetos negros . Under this viewpoint of comprehension of the spatial element, we carried out a study about the notion of paradise associated to Brazil. At this part of the dissertation, we considered relevant to carry out a historical/literary study about some texts which represent this notion dating back to Britto production, which, somehow, relativizes and recreates this ideology. Besides characterizing the space of the book Paraísos artificiais we will also take into consideration the profiles of the characters present in the short-story, subjects who seem to have lost their identity. In order to do that, we make use of some theoretical presuppositions about postmodernity, such as Linda Hutcheon, Zygmunt Bauman, Marshall Berman, Stuart Hall, Frederic Jameson, Marisa Martins Gama Khalil, Jean-François Lyotard and Jair Ferreira dos Santos. We will make some considerations about Foucault notion of space as well as Gaston Bachelard, Deleuze and Guattari, Berrettini, Schorske, Renato Cordeiro Gomes, among others.